Motivasi Perawat dalam Pemenuhan Kebutuhan Spiritual pada Klien di Ruang Rawat Inap Rumah Sakit Daerah Balung (Nurses Motivation to Patients Spiritual Needs Fulfillment at Balung Hospital) - Ahmat Robbi Tricahyono; Retno Purwandari; Mulia Hakam (Pustaka Kesehatan, 2015)
Nursing care is done by considering individuals as the holistic (bio-psycho-socio-spiritual) creature, particularly in fulfilling spiritual needs. This research was intended to analyze the relationship between the nurses motivation and patients spiritual needs fulfillment at Balung Hospital. This research applied observational analytic method with cross sectional. Sampling technique used total sampling by involving 48 respondents. Data was analyzed using nonparametric Chi Square. The result of the analysis reveal that the majority of the motivation of the nurses was influenced by extrinsic motivation, 72,7% of high motivation and good spiritual fulfillment, 38,5% of low motivation was good spiritual fulfillment, 61,5% of low motivation was bad spiritual fulfillment, and 27,3% of high motivation was bad spiritual fulfillment. Results of statistical analysis showed that the p-value is 0,037 (α=0,05) which indicates the relationship between nurses motivation and spiritual needs fulfillment to patients at Balung Hospital. Fulfilling spiritual needs is an important aspect in the process of treating the clients. It is the nurse’s duties to observe then fulfill the patients spiritual needs. Hence, coordination with other medical team through various discussions is an immediate importance. Nurses are expected to meet the patients needs of spiritual aspects in order to achieve a more holistic nursing care.   Keywords: nursing care, motivation, spiritual fulfillment